THE INFLUENCE OF ESSENTIAL AMINO ACIDS ON POLLARD-CORN FEED BASE TO THE BODY DIMENSIONS OF THE BALI PIG - I K. L., Lewis; Sumadi, I K.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2020)
This research is intend to find out the influence of the lysine, methionine, and the tryptophan amino acid supplementation on the pollard corn base ration to the dimension of the male Bali pig. This research was held for 12 weeks in Jalan Kresna, Banjar Batuparas, Desa Padang Sambian Kaja. The design that is used is the completely randomized design with 3 different handlings, they are P0 ( 50% yellow corn + 49% pollard + 0,5% NaCl and + 0,5 % mineral mixture ), PI ( 50% yellow corn + 49% pollard + 0,5% NaCl + 0,5 % mineral mixture + lysine amino acid + methionine + tryptophan ), P2 ( Recommended ration with the ME/CP ratio = 2800 kcal/kg/16% ) which is repeated for 4 times, and each repetition consist of 1 livestock, so it used 12 male Bali pigs. The variable that was being observed is the dimension of the bali pig body, which are the chest size, stomach circumference, shoulder height, back height, hip height, and the body length. The result of the research shows that the supplementation of the lysine, methionine, and tryptophan amino acid on the dimension of the bali pig have a significant influence (P<0,05) on the variables that are the chest size, body length, shoulder height, stomach circumference, back height, and the hip height. Based on the result of the research we can conclude that the addition of the lysine, methionine, tryptophan amino acid on the pollard corn base ration can increase the dimension of bali pig body which are the chest size, body length, shoulder height, stomach circumference, back height, and the hip height. Key w ord s : b ali pig, body dimension, (lysine amino acid, methionine, and the tryptophan) supplementation .